A DESCRIPTIVE ANALYSIS OF CURRENT LIS EDUCATION PROVIDERS AND PROGRAMMES IN SRI LANKA - Wijetunge, Pradeepa (Malaysian Journal of Library and Information Science, 2009)
Formal Library and Information Science (LIS) education in Sri Lanka began in 1961 with the commencement of a short programme by the Sri Lanka Library Association (the then Ceylon Library Association). From 1961 to 1997, many programmes were introduced but some were terminated due to various reasons. The introduction of new LIS programmes was accelerated from 1997 onwards as a result of the reforms in the education system which brought significant changes in LIS education. There were many issues affecting the LIS education system of Sri Lanka but without due attention of the authorities. In order to understand the issues concerning the LIS education system in a holistic manner; a research project was carried out from the year 2004 to 2007. Several aspects regarding LIS education were studied in depth, for example, the current available LIS programmes and providers, course contents, LIS faculty and facilities. This paper presents the current status of LIS providers and programmes in the country. Eight university and non university LIS education providers were identified from a survey. At the university level there are six organizations; the National Institute of Library and Information Sciences, the Department of LIS affiliated to a university faculty, two faculties offering several postgraduate level LIS programmes, and two units affiliated to universities. At the non-university level there are two types of organizations (an association and three colleges) conducting the programme – the Sri Lanka Library Association and three National Colleges of Education. The survey also identified a total of 24 programmes at six different academic levels comprising six Certificate programmes, six Diploma programmes, three Bachelors programmes, three Post Graduate Diploma programmes, four Masters programmes and two Research Degree programmes. The paper highlights the absence of a co-ordinating body for LIS education in Sri Lanka and it concludes by identifying a suitable body for this purpose.